Os estilos de liderança e a influência do líder na equipe de tratamento de água e esgoto no município de Carapicuíba - SILVEIRA, João Gabriel; SANTOS, Samuel Flaviano Rocha; REIS, Vinicius Rodrigues (245, 2025)
O presente trabalho tem como objetivo compreender os estilos de liderança exercidos pelos gestores que influenciam o desempenho diário da equipe responsável pelo tratamento de água e esgoto em Carapicuíba, município da Grande São Paulo. O saneamento básico é essencial para proporcionar saúde e dignidade à população, e seu bom funcionamento depende também das pessoas que atuam diretamente na operação. A pesquisa aborda teorias clássicas e modernas de liderança — autocrático, democrático, liberal, transformacional e transacional — analisando como cada tipo de liderança impacta fatores como motivação, produtividade, comunicação e clima organizacional. A metodologia inclui entrevistas e questionários com gestores e funcionários da área, buscando compreender a relação entre práticas de liderança e desempenho coletivo. Espera-se que os resultados contribuam para o aprimoramento da gestão pública, destacando a importância de lideranças humanas, participativas e preparadas para os desafios do saneamento básico.

This study aims to analyze the leadership styles adopted by managers of the water and sewage treatment team in the municipality of Carapicuíba, São Paulo, and how these styles directly influence employee performance, motivation, and organizational climate. Basic sanitation is an essential service for public health and quality of life, and its effectiveness depends not only on infrastructure and technology but also on human resource management. The research is based on classical and contemporary leadership theories, such as those by Lewin, Lippitt, and White (1939), who describe autocratic, democratic, and laissez-faire styles, as well as transformational and transactional leadership models by Bass and Avolio (1994). The methodology combines quantitative instruments, such as structured questionnaires for employees, and qualitative tools, such as interviews with area leaders. Data analysis seeks to understand which leadership practices foster better employee engagement and team performance, and what challenges must be addressed to strengthen leadership culture in the public sector. The results are expected to support the development of professional training and workforce development policies in municipal sanitation, contributing to continuous service improvement for the local population.
Leadership styles and the influence of the leader on the water and sewage treatment team in the municipality of Carapicuíba
Keywords: Liderança; Tratamento de água; Tratamento de esgotos sanitários; Administração; Gestão e Negócios